TRENDS OF POSTGRADUATE THESES ON EARLY CHILDHOOD MATHEMATICS EDUCATION IN TURKEY (Third Sector Social Economic Review, 2025)
The aim of the research is to synthesize and evaluate these studies at the postgraduate level in the field of mathematics education during early childhood in Turkey. It was conducted using a systematic review method. The postgraduate theses related to mathematics education during early childhood in Turkey form the population of the study, encompassing 168 theses from 1986 to 2023. A Thesis Review Form prepared by the researchers was used during the data collection process, and the obtained data were analyzed using descriptive content analysis. It was found that 125 of the theses were master's theses and 43 were doctoral theses. Analyzing the publication years of the research shows a rising interest and intensity, particularly after 2011, indicating an increase in the number of researchers in this field. The most commonly used methods in the studies were identified as quantitative, mixed, and qualitative methods in that order. The diversity and prevalence of postgraduate research in mathematics education during early childhood in Turkey underline the importance and necessity of this field. However, the low number of doctoral-level studies suggests a need to focus more on doctoral research in the future.
Keywords: Early childhood; Mathematics in early childhood; Postgraduate; Theses; Trends.